Using the internet among dental students in Yazd - Jamshid Ayatollahi; Fatemah Ayatollahi; Rezvan Bahrololoomi (Wolters Kluwer Medknow Publications, 2010)
Background : Internet is an important source of up-to-date dental information for delivering educational materials. The aim of this study was to determine the use of internet among dental students in Yazd. Methods : In this descriptive study, a questionnaire consisting of multiple choice questions was distri-buted to clinical undergraduate students studying at the School of Dentistry at the Shahid Sadoughi University of Yazd, Iran in 2009. The chi-square test was used to compare the frequency of internet use between the two genders. The level of statistical significance for all tests was set at 0.05. Results : Seventy-nine percent of the students used the internet in various frequencies. In general, female students used the internet more often than their male counterparts (P < 0.0001). Although 13.79 percent of students used the internet to retrieve general information, dental topics were searched in the internet more frequently. The texts were the most commonly accessed materials (73.9 percent). Clinical photographs were accessed by 47.9 percent and radiographic and histopathologic materials by 12.3 and 10.9 percent of the students, respectively. Our students stated that they could find required information on dental subjects in English sites (96.6 percent) much more frequently than in the Farsi sites (78 percent).Conclusion : The results of this study reflect the attitudes of dental students to internet use as a part of their education in Shahid Sadoughi University of Yazd.